Inequities and psychiatry disability in transition among the elderly population from 1987 to 2006 in China: Data based on national surveys. Issue 36 (September 2016) - Wang, Zhenjie; Li, Ning; Guo, Chao; Zhang, Lei; Chen, Gong; Zheng, Xiaoying
Abstract : Abstract: The world will be facing huge population aged 65 and older, accounting for 13% of the total population in the future. Significant disabilities rates reflect an accumulation of health risks. Psychiatry disability is one of the most significant disabilities, because it manifests in cognitive, affective, and behavior disorders that limit one's daily life and restrict their participations. Very few studies have explored the 20 years associations between demographic factors and psychiatry disability among older people in China. In this study, we investigated psychiatry disability transitional association behind China rapid development from 1987 to 2006 among the 60 and older population. Data used 2 nationally represented, population-based data from the China National Sample Surveys on Disability, conducted in 1987 and 2006. The sample size of the current study was 140, 008 in 1987 and 354, 859 in 2006, respectively. Associations between socioeconomic factors and psychiatry disability were determined by using a logistic regression model. The prevalence of psychiatric disabilities increased from 1987 to 2006. In both surveys, the most common psychiatric disabilities were schizophrenia, schizotypal, and delusional disorders, and they presented the same associations with age increase. Socioeconomic inequities, such as current employment status and marital status, were associated with psychiatry disability in both surveys. These associations remained even after these 2 surveys were combined. The rapidly rising prevalence of psychiatric disorders expected warrants strategies to reduce the burden of these disabilities among females and rural residents.